2011
DOI: 10.1111/j.1530-0277.2011.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Strain Differences in Developmental Vulnerability to Alcohol Exposure via Embryo Culture in Mice

Abstract: Background Prenatal alcohol exposure can result in varying degrees of neurodevelopmental deficits, growth retardation, and facial dysmorphology. Variation in these adverse outcomes not only depends on the dose and pattern of alcohol exposure but also on less well understood interactions among environmental, genetic, and maternal factors. The current study tested the hypothesis that fetal genotype is an important determinant of ethanol teratogenesis by evaluating effects of ethanol exposure via embryo culture i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 43 publications
5
47
0
Order By: Relevance
“…Many key genes encoding important morphogen and neurotrophic factors, which are important for differentiation and growth, are located in the floor plate of the neural tube (e.g., the sonic hedgehog and neurotrophic factor fibroblast growth factor; Ye et al, 1998;Dessaud et al, 2008). Temporally, the long alcohol exposure (44 hours) resulted in more severe growth retardation than the shorter (6 hours) alcohol exposure in comparing this and previous studies (Chen et al, 2011). The longer inhibition of DNA methylation also resulted in greater growth delay (Table 2).…”
Section: Dna Methylation Program and Altered Statementioning
confidence: 58%
“…Many key genes encoding important morphogen and neurotrophic factors, which are important for differentiation and growth, are located in the floor plate of the neural tube (e.g., the sonic hedgehog and neurotrophic factor fibroblast growth factor; Ye et al, 1998;Dessaud et al, 2008). Temporally, the long alcohol exposure (44 hours) resulted in more severe growth retardation than the shorter (6 hours) alcohol exposure in comparing this and previous studies (Chen et al, 2011). The longer inhibition of DNA methylation also resulted in greater growth delay (Table 2).…”
Section: Dna Methylation Program and Altered Statementioning
confidence: 58%
“…Research has shown that teratogenic effects of PAE can be influenced by multiple maternal factors, including hormone status (particularly hormones of the HPA axis), nutrition, oxidative stress level, age, parity and years of drinking [117][118][119][120]. Genetic profiles of both mother and fetus may also alter the metabolism of alcohol and risk of physical birth defects, prenatal mortality, learning and other neurobehavioral deficits in the offspring [121][122][123]. Familial patterns of heavy drinking during pregnancy, which may be associated with family and cultural customs, may also result in an increased incidence of ND-PAE.…”
Section: Familial Patternmentioning
confidence: 98%
“…P renatal alcohol exposure causes fetal alcohol spectrum disorders (FASD) in up to 2-5% of school-age children and is the leading preventable cause of mental retardation in the Western world (1,2). The prevalence and presentation of FASD are influenced by the quantity, frequency, and timing of drinking and are modified by a variety of environmental, nutritional, epigenetic, and genetic factors (3)(4)(5)(6)(7). The observation that there is greater concordance for fetal alcohol syndrome (FAS) in monozygotic twins than in dizygotic twins suggests that there are susceptibility genes for FASD (8); however, their identification remains elusive.…”
mentioning
confidence: 99%